The question of MacArthur's reputation Côte de Châtillon, October 14-16, 1918 - Ferrell, Robert H. (University of Missouri Press, 2008)
"Ferrell examines the WWI battle at Côte de Châtillon, reconstructing the movements of troops and the decisions of officers to detail how MacArthur's subordinates were the true heroes and how the taking of the hill could have been a disaster had the Eighty-fourth Brigade followed the general's original plan"--Provided by publisher.